Effect of stress inoculation training on the levels of stress, anxiety, and depression in cancer patients - Fahimeh Kashani; Parisa Kashani; Maryam Moghimian; Mahsa Shakour (Wolters Kluwer Medknow Publications, 2015)
Background: Cancer is a broad group (over 270 types) of diseases. This disease, like other chronic diseases, occurs in all ages and ethnic groups, and is considered as a major health problem. Stress is one of the most important psychological factors influencing the occurrence of physical diseases, and can lead to severe anxiety, depression, and negative effects on health. It can also make individuals vulnerable to physical diseases, and in the long term, leads to death. This study was conducted to determine the effect of inoculation training on stress, anxiety, and depression in cancer patients. Materials and Methods: This study was conducted in 2013 as a clinical trial with convenient random sampling of patients from the chemotherapy clinic of Seyed Al-Shohada hospital of Isfahan. Forty patients with cancer who were eligible for the study were randomly assigned to either case or control group. The case and control groups had the same treatment plans, and the only difference was stress inoculation training administered in the case group, which was composed of eight 90-min sessions over 8 weeks. Data were collected using Depression, Anxiety, Stress Scales 42 (DASS-42) questionnaire and demographic questionnaire, and analyzed by analysis of covariance (ANCOVA) and t-test in SPSS. Results: The results showed that there was a significant difference between case and control groups in terms of stress, anxiety, and depression ( P < 0.001). Stress inoculation training reduced stress, anxiety, and depression in cancer patients. Conclusions: Stress inoculation training significantly reduced stress, anxiety, and depression. Therefore, teaching this skill and the strategies of coping with stress is recommended for these patients, in addition to medicational treatment.